Group Decision-Making Model Based on Triangular Neutrosophic Sets for Service Quality Evaluation in Tourism Mobile E-Commerce - Liu, Ying (Neutrosophic sets and systems, 2025)
Triangular fuzzy numbers are frequently used by experts to assess their opinions in the group decision-making (GDM) paradigm. In this research, we used neutrosophic because preference connections with triangular fuzzy numbers are consistent. In GDM, it is crucial to consider the degree of consensus and the consistency of expert opinion. The idea of additive approximation consistency is put out for triangular neutrosophic Sets (TNSs) additive reciprocal matrices to differentiate the typical consistency. The GDM methodology is used to evaluate tourism mobile e-commerce services to select the best one. Two methods are used in this study such as SWARA is used to compute the criteria weights and the WASPAS method is used to rank the alternatives. 12 criteria and 7 alternatives are collected in this study to be evaluated. The results of the sensitivity analysis which is applied in this study show the stability of the rank of alternatives under different cases. Keywords: Triangular Neutrosophic Sets (TNSs); Uncertainty; WASPAS; SWARA; Tourism Mobile E-Commerce.